Characterization of DLL3-positive circulating tumor cells (CTCs) in patients with small cell lung cancer (SCLC) and evaluation of their clinical relevance during front-line treatment. (September 2019) - Messaritakis, Ippokratis; Nikolaou, Michalis; Koinis, Fillipos; Politaki, Eleni; Koutsopoulos, Anastasios; Lagoudaki, Eleni; Vetsika, Eleni- Kyriaki; Georgoulias, Vassilis; Kotsakis, Athanasios
Highlights: DLL3 is considered as Trojan horse for potent therapeutic implication. An important heterogeneity of CTCs was demonstrated in patients with SCLC. Changes of DLL3 + CTCs on treatment seem to be of prognostic importance. Abstract: Objectives: The aim of the study was to characterize and evaluate the presence of DLL3-positive Circulating Tumor Cells (CTCs) in SCLC patients receiving front-line chemotherapy and assess their clinical relevance. Materials and methods: Peripheral blood was obtained from treatment-naïve patients with SCLC (n = 108 patients), after one etoposide/platinum cycle (n = 68 patients) and on disease progression (n = 48 patients). Immunofluorescence staining using antibodies against the DLL3, cytokeratins (CK), CD45 and vimentin (Vim) was used for the detection and characterization of CTCs. Results: Before treatment, 74.1% of patients had detectable DLL3 + /CD45 − CTCs. One-treatment cycle significantly decreased both the detection rate ( p  < 0.001) and the absolute number ( p  < 0.001) of DLL3 + /CD45 − CTCs. Triple immunofluorescence staining using anti-CK, anti-Vim and anti-DLL3 antibodies revealed an important CTC heterogeneity since DLL3 could be detected in Vim +, Vim −, CK + and CK − CTCs. On disease progression, both the detection rate and the absolute number of DLL3 + /CD45 − CTCs were significantly increased compared to post-1 st cycle values ( p  < 0.001 and p  = 0.002, respectively). In addition, 22.7% of patients had detectable DLL3 + /CD45 − cells which could not be captured by the CellSearch assay. In multivariate analysis, the detection of DLL3+/CD45- CTCs at baseline was significantly associated with decreased progression-free survival (HR = 10.8; p  = 0.005) whereas their detection on disease progression was associated with decreased overall survival (HR: 28.2; p  = 0.016). Conclusions: These findings demonstrate an important heterogeneity of CTCs, based on the expression of CK, Vim and DLL3, in patients with SCLC and the changes of DLL3 + /CD45 − CTCs during treatment seem to be a dynamic biomarker associated with patients' clinical outcome.